2022
DOI: 10.1007/s00127-022-02256-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding differences in mental health service use by men: an intersectional analysis of routine data

Abstract: Purpose Rates of help-seeking for common mental health problems are lower for men, but less is known about patterns of engagement once they are in contact with services. Previous research has been limited in its ability to understand the intersection between service user characteristics and engagement. This study compared analytic approaches to investigate intersectional associations between sociodemographic and socioeconomic indicators and use of psychological treatment services by men. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In this context, we found that intersections relating to experiences of racism, migration, fragile social circumstances, complex trauma, social marginalisation, the important role of religion in a person’s life, and English language proficiency were more conceptually important and useful than crude ethnic group classifications. A recent quantitative study exploring mental health service use in men also found important intersections between social deprivation, religion, and ethnicity [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we found that intersections relating to experiences of racism, migration, fragile social circumstances, complex trauma, social marginalisation, the important role of religion in a person’s life, and English language proficiency were more conceptually important and useful than crude ethnic group classifications. A recent quantitative study exploring mental health service use in men also found important intersections between social deprivation, religion, and ethnicity [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…R/S is a complex phenomenon with multidimensional and multi-stratificational characteristics having disparate roles and impacts in different populations and R/S groups [ 29 ]. Consequently, the social and psychological aspects of R/S may have disparate functions in the individual’s life [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite having poorer mental health, Indigenous peoples and other ethnic minorities are often under-users of mental health services [ 25–28 ] or have an increased risk of disengaging from treatment [ 29 ]. This phenomenon is often due to language and cultural barriers, the lack of culturally sensitive services, alternative aetiological conceptions of mental diseases, social stigma, and mistrust towards Western psychiatry [ 25 , 26 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort was formed of those who have completed a course of treatment (at least two IAPT treatment sessions as per previous research and NHS Digital guidelines 26 , 27 ). When individuals had received several courses of IAPT treatment between 2012 and 2019, the first course of treatment was considered as per previous research 28 to maximise the length of the study follow-up. As prevalence of CVD rises between the age of 45 and 54, 29 individuals were included in the analytic cohort if they were over 45 years of age at the time of IAPT referral, had completed depression symptom measures pre- and post-treatment, and had at least one linked HES or ONS record available.…”
Section: Methodsmentioning
confidence: 99%